Crystal structures of the 1:1 salts of 2-amino-4-nitrobenzoate with each of (2-hydroxyethyl)dimethylazanium, tert-butyl(2-hydroxyethyl)azanium and 1,3-dihydroxy-2-(hydroxymethyl)propan-2-aminium - Wardell, James L.; Tiekink, Edward R. T. * (International Union of Crystallography, 2018)
The crystal and molecular structures of the title molecular salts,C4H12NO+C7H5N2O4, (I), C6H16NO+C7H5N2O4, (II), and C4H12NO3+-C7H5N2O4, (III), are described. The common feature of these salts is thepresence of the 2-amino-4-nitrobenzoate anion, which exhibit non-chemicallysignificant variations in the conformational relationships between the carboxylate and nitro groups, and between these and the benzene rings they are connected to. The number of ammonium-N—H H atoms in the cations increases from one to three in (I) to (III), respectively, and this variation significantly influences the supramolecular aggregation patterns in the respective crystals. Thus, a linear supramolecular chain along [100] sustained by charge-assisted tertiary-ammonium-N—HO(carboxylate), hydroxy-O—HO(carboxylate) and amino-N—HO(carboxylate) hydrogen-bonds is apparent in the crystal of (I). Chains are connected into a three-dimensional architecture by methyl-C—HO(hydroxy) and – interactions, the latter between benzene rings [intercentroid separation = 3.5796 (10) A˚ ]. In the crystal of (II), a supramolecular tube propagating along [901] arises as a result of charge-assisted secondaryammonium-N—HO(carboxylate) and hydroxy-O—HO(carboxylate) hydrogen-bonding. These are connected by methylene- and methyl-C— HO(nitro) and – stacking between benzene rings [inter-centroid separation = 3.5226 (10) A˚ ]. Finally, double-layers parallel to (100) sustained by charge-assisted ammonium-N—HO(carboxylate), ammonium-N—H O(hydroxy) and hydroxy-O—HO(carboxylate) hydrogen-bonds are apparent in the crystal of (III). These are connected in a three-dimensional architecture by amine-N—HO(nitro) hydrogen-bonds.